The Impact Of Green Marketing Campaign Towards H&M Indonesia Customers’ Purchase Decision: A Case Study On H&M Conscious Collection - Daniella Lay, Stephanie (CV. Publikasi Indonesia, 2024)
In recent years, the topic of sustainability has been on the rise. As it continues to become an area of concern and discussion, industries are also nudged, and even forced, to go in the same direction in order to keep up with the competition. This has also been complemented with how people are now more interested in sustainable brands, in which being sustainable has now become a trend as more and more companies decide to go green, and even a priority. Amongst them is the fashion industry; H&M was first accused of greenwashing in August of 2019 by The Norwegian Consumer Authority as it defines its Conscious Collection as “the shortcut to more sustainable shopping”. This research would like to investigate if greenwashing; described as making false claims about a brand’s product or service to attract more customers; affects the purchase decision of customers. This research employs a quantitative methodology with non-probability sampling by contacting H&M Indonesia Twitter followers. The results of this research revealed that the greenwashing done by H&M through its Conscious Collection green marketing campaign did not play a significant role in the purchase decision of H&M Indonesia customers due to Indonesians’ environmental literacy. It is hoped that the implications of this research help to advise big corporations as well as small aspiring businesses that being sustainable should be done correctly and genuinely – from communicating green promotional messages to executing a green marketing campaign.